2015
DOI: 10.15740/has/tajh/10.2/286-291
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant growth regulators on flower yield, vase life and economics of dutch rose (Rosa hybrida Linn.) cv. ‘PASSION’ under polyhouse condition

Abstract: Click www.researchjournal.co.in/online/subdetail.html to purchase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Variation in fresh weight of many varieties is attributed to the differences in genetic characters of the varieties. Similar result were reported by Luo et al [8], Kazaz et al [9] and Baidya et al [10] in Rose [11,12,13].…”
Section: Fresh Weight Of Flower (G)supporting
confidence: 89%
“…Variation in fresh weight of many varieties is attributed to the differences in genetic characters of the varieties. Similar result were reported by Luo et al [8], Kazaz et al [9] and Baidya et al [10] in Rose [11,12,13].…”
Section: Fresh Weight Of Flower (G)supporting
confidence: 89%
“…Similar findings were observed by Sharma et al [18] in Apple clonal rootstocks and Bharathy et al [19] in carnation plants. These results are supported by the findings of Gupta et al [20] in Nerium, Netam et al [21] in Jasmine, Bosila et al [22] in Bougainvillea, Susila et al [23] in Adathoda and Parmar et al [24] in Bougainvillea.…”
Section: Average Length Of Roots Per Cutting (Cm)supporting
confidence: 85%
“…(Hashemabadi and Zarchini, 2010) showed that pre-harvest use of gibberellic acid, salicylic acid, and cycocel significantly increased the number of flower branches in the experimental unit as the concentration of 200 ppm gibberellic acid caused 56.08% performance per square meter per year is higher than the control. (Parmar et al, 2015) found that treatment with 200 ppm of gibberellic acid was the most effective treatment for increasing the number of flowers per plant, the number of flowers per square meter of land, and the number of flowers per hectare in the rose flower cv. "Passion", which increased 15 times higher than control.…”
Section: Number Of Branches Per Plantmentioning
confidence: 99%